2016
DOI: 10.1126/scitranslmed.aaf9440
|View full text |Cite
|
Sign up to set email alerts
|

Senescence-associated secretory phenotype contributes to pathological angiogenesis in retinopathy

Abstract: Pathological angiogenesis is the hallmark of diseases such as cancer and retinopathies. Although tissue hypoxia and inflammation are recognized as central drivers of vessel growth, relatively little is known about the process that bridges the two. In a mouse model of ischemic retinopathy, we found that hypoxic regions of the retina showed only modest rates of apoptosis despite severely compromised metabolic supply. Using transcriptomic analysis and inducible loss-of-function genetics, we demonstrated that isch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
169
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 210 publications
(181 citation statements)
references
References 77 publications
12
169
0
Order By: Relevance
“…Overexpression of either arginase isoform has been reported to promote senescence of HUVEC [15,16]. An association between diabetes and the development of SASP in retinal cells has also been reported [17,18]. However, the underlying mechanisms are not yet understood.…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of either arginase isoform has been reported to promote senescence of HUVEC [15,16]. An association between diabetes and the development of SASP in retinal cells has also been reported [17,18]. However, the underlying mechanisms are not yet understood.…”
Section: Introductionmentioning
confidence: 99%
“… found that retinal ischemia can trigger cellular senescence to protect retinal cells, which enables retinal cells to survive periods of limited metabolic supply and to escape hypoxia‐associated cell death in a mouse model of ischemic retinopathy. Interestingly, using transcriptome analysis combined with loss‐of‐functions genetics, Oubaha's results indicated that those cells require the activity of the endoribonuclease domain of IRE1α to promote senescence and adopt a senescence‐associated secretory Phenotype (SASP) . The presence of SASP‐associated cytokines, such as plasminogen activator inhibitor‐1 (PAI‐1), interleukin‐6 (IL‐6), interleukin‐8 (IL‐8), and VEGF were found to be present in the vitreous humor of patients suffering from proliferative DR.…”
Section: Chapter 5: Functional Role Of Er Stress During Cellular Senementioning
confidence: 99%
“…Furthermore, they identified a clinical relevance of SASP inhibition using metformin, a widely used biguanide antidiabetic drug known to reduce SASP without interfering with the growth arrest program . They demonstrated that intravitreal injection of metformin into mice abolished SASP, decreased ER stress, and reduced retinal neovascularization and pathological retinal angiogenesis .…”
Section: Chapter 5: Functional Role Of Er Stress During Cellular Senementioning
confidence: 99%
See 2 more Smart Citations